(untitled) (Homiletic, 2020)
As the saying goes, “A picture is worth a thousand words.” However, the printed word—more specifically, scripture—has been the traditional base of the sermon. Through a personal experience reflection, this paper advocates using artwork as the foundational text for sermons, and presents an approach to art exegesis based on the practical method of art criticism. Employing art historian and educator Edmund Burke Feldman’s approach to art criticism, the authors present a step-by-step exegesis of an artwork that mirrors the exegesis of biblical texts, including selecting an artwork, exegeting the art, choosing a theme and sermon form, and developing an introduction and conclusion. The authors further illustrate that preachers can create sermons that are faithful to their personal theologies and faith traditions even when using art, rather than the Bible, as foundational texts.